2008
DOI: 10.1590/s1516-18462008000200010
|View full text |Cite
|
Sign up to set email alerts
|

Perfil vocal de regentes de coral do estado de São Paulo

Abstract: OBJETIVO: traçar o perfil vocal de regentes de corais do Estado de São Paulo. MÉTODOS: participaram deste estudo 150 regentes de corais do Estado de São Paulo. A coleta foi feita individualmente pelo mesmo avaliador, nos locais de trabalho dos entrevistados, através de questionário fechado. RESULTADOS: os regentes tem em média 8,4 anos de exercício da profissão, regem 1 coral e já fizeram de 1 a 5 anos de aula de canto. Ensaiam os naipes em separado, cantam junto com os naipes, fazem aquecimento e não fazem de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 13 publications
(19 reference statements)
1
7
0
12
Order By: Relevance
“…In the present study, 65% of the individuals reported not knowing how the voice is produced and, consequently, did not know all the factors that contribute to a good vocal health, a fact that is in accordance with the literature that was researched 3 . On the other hand, it was found that all choir singers performed vocal warm up exercises.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, 65% of the individuals reported not knowing how the voice is produced and, consequently, did not know all the factors that contribute to a good vocal health, a fact that is in accordance with the literature that was researched 3 . On the other hand, it was found that all choir singers performed vocal warm up exercises.…”
Section: Resultssupporting
confidence: 88%
“…(2) Federal University of São Paulo -UNIFESP, São Paulo, SP, Brasil. (3) Federal University of São Paulo -UNIFESP, São Paulo, SP, Brasil.…”
Section: Caracterização Dos Aspectos Vocais De Um Coro Infantojuvenilmentioning
confidence: 99%
“…A verificação dos critérios de inclusão e de exclusão foi realizada por meio da aplicação de questionário, elaborado com base na literatura 9,[17][18][19] com perguntas abertas e fechadas sobre os dados de identificação, sexo, idade, tipo de canto, categoria profissional ou amadora.…”
Section: Introductionunclassified
“…The slight to moderate voice alterations identified by the GRBASI scale and noticed by some operators in the sample may be related to the results of the otorhinolaryngologic evaluation. The accumulation of secretion on the vocal folds -the most prevalent laryngeal image in this study -is characteristic of professional voice users and the mucus formed on the vocal folds is a protective reaction in face of the voice behavior (26) . The accumulation of secretion shown by the video laryngoscopy altered some of the parameters analyzed in the perceptual-auditory evaluation such as overall degree, roughness, and instability.…”
Section: Discussionmentioning
confidence: 84%